Biologi dan kelimpahan tungau merah Tetranychus sp. (Acari: Tetranychidae) pada dua kultivar jarak pagar (Jatropha curcas) - Sugeng Santoso; Aunu Rauf; Nelly Mastina Gultom; Elna Karmawati; Widi Rumini (Perhimpunan Entomologi Indonesia, 2014)
Red spider mite Tetranychus sp. is one of the most important pests attacking leaves of Jatropha curcas. The objective of this study was to elucidate life history parameters and abundance of spider mite on two J. curcas cultivars. Field studies were carried out in BALITTRI Pakuwon Sukabumi, and laboratory experiments were conducted at the Department of Plant Protection, Bogor Agricultural University, from June to November 2008. Cultivars significantly affected several life history parameters of the spider mite. Spider mite reared on IP1-P cultivar have longer oviposition period and higher fecundity than those on IP2-P (7.00 days and 25.56 eggs against 5.00 days and 10.00 eggs). The sex ratio of spider mite was 3.2 : 1 on IP1-P and 2.5 : 1 on IP2-P. Intrinsic rate of increase was also higher on IP1-P. However, field studies indicated that the spider mite were less abundant on this cultivar. These might be due to the presence of other arthropods which were higher on IP1-P. In general, the highest population of spider mite occurred in August and the lowest in October–November. Predatory mite Family Phytoseiidae was found associated with spider mite, however its role as natural control agent was not significant.